2021
DOI: 10.1007/s10943-021-01188-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Baseline Patterns of Spiritual Coping, Forgiveness, and Gratitude on the Completion of an Alcohol Addiction Treatment Program

Abstract: The purpose of this study was to identify distinct profiles of persons beginning alcohol addiction therapy with similar baseline configurations of spiritual coping, forgiveness, and gratitude. The associations between latent profile membership and the completion of therapy were also examined. The sample was composed of 358 alcohol-dependent persons receiving an outpatient treatment program. The Spiritual Coping Questionnaire, the Forgiveness Scale, and the Gratitude Questionnaire were used to assess the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Practitioners engage in purposeful interaction with their day, giving thanks for positive aspects of their lives. In the context of addiction treatment, patients regularly experience guilt and shame arising from their past actions, and teaching gratitude practices to patients could help them reverse these effects (Charzyńska, 2021;Emmons & Mishra, 2011;Kraiss et al, 2023). 3. Review: Attending to daily events and emotions.…”
Section: The Ignatian Examenmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners engage in purposeful interaction with their day, giving thanks for positive aspects of their lives. In the context of addiction treatment, patients regularly experience guilt and shame arising from their past actions, and teaching gratitude practices to patients could help them reverse these effects (Charzyńska, 2021;Emmons & Mishra, 2011;Kraiss et al, 2023). 3. Review: Attending to daily events and emotions.…”
Section: The Ignatian Examenmentioning
confidence: 99%
“…The next step of the Examen practice is to review one's day with an emphasis on gratitude (Fuchs et al., 2023; Plante, 2021), asking oneself, for instance, “Where can I look for hidden blessings that I might otherwise take for granted?” Practitioners engage in purposeful interaction with their day, giving thanks for positive aspects of their lives. In the context of addiction treatment, patients regularly experience guilt and shame arising from their past actions, and teaching gratitude practices to patients could help them reverse these effects (Charzyńska, 2021; Emmons & Mishra, 2011; Kraiss et al., 2023). Review : Attending to daily events and emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual development is correlated with gratitude. Gratitude is understood as a life orientation to recognize and value the positive aspects of one's life and the world [55]. Those who feel spiritually supported by God have a variety of positive mental health characteristics, including less depression, lower levels of psychological stress, a lack of feelings of loneliness, and high self-esteem.…”
Section: Multimodal Discourse Analysismentioning
confidence: 99%
“…Similarly, forgiving therapy can help patients reduce emotions that lead to anger (Wijaya & Widiyastuti 2020). This has to do with spirituality, where forgiving therapy becomes an adaptable treatment for a person with an addictive disorder (Charzynska, 2021).. Other studies have found a positive impact of forgiveness that can change a person's behavior caused by mental abuse such as bullying (Watson, Todorov, & Rapee, 2020). Even forgiving therapy is effective for victims of emotional abuse (Ha, Bae, & Hyun, 2019).…”
Section: It Is Good To Forgive Oneself and Others For Addictsmentioning
confidence: 99%